Analisis Pemahaman Guru IPA se-Kecamatan Lima Kaum terhadap Pelaksanaan Standar Proses dan Standar Penilaian Kurikulum 2013 - Yudistia Ariany; Ardi Ardi; Yosi Laila Rahmi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
In the 2013 curriculum the learning process uses 21st century skills, while for the assessment process uses authentic assessment. Based on the observation of class VII SMP Negeri in Lima Kaum Tanah Datar district, the teachers in the school have not fully implemented the Curriculum 2013. This resulted in a gap in the compliance of National Education Standards, especially on process standards and assessment standards.The aim of this research is a describe the understanding of science teachers in implementing the 2013 Curriculum in the class VII especially on standard process and assessment standard. This research was conducted in junior high school in Kecamatan Lima Kaum Tanah Datar. The population in this research is science teacher in class VII consisting of 8 science teachers.The sampling technique used is total sampling. Data collection techniques used questionnaires and document analysis. The data obtained were analyzed using percentage technique and made according to the descriptive sub indicator.The results revealed the understanding of science teachers on the implementation of Curriculum 2013 class VII in SMP Negeri Se-Kecamatan Lima Kaum Tanah Datar. 1. Understanding of science teachers on the implementation of Curriculum 2013 based on process standard that is 80,5% with good criteria. 2. Understanding of science teachers on the implementation of Curriculum 2013 based on the standard assessment is 83.4% with good criteria.